Water desalination as an option to balance the water demand and supply equation of Jordan - (:unkn) unknown (DESALINATION PUBL, 2019)
Jordan is facing an increasing and serious threat of water shortage while its population has almost doubled over the last decade. The adoption of nonconventional water supply technologies such as desalination is unavoidable. In this review, key facts of current water desalination status are highlighted, in the context of a comprehensive review of water desalination in Jordan in the past. Future needs are then discussed taking into consideration the potential of available water sources and economic drivers for the next generation. Performance of two existing desalination plants for drinking water purposes was evaluated. Due to current and projected water shortages, water desalination has a great potential to balance the water demand and supply equation in Jordan. This analysis suggests that Jordan will have to depend significantly expanding its desalination capacity for reliable water supply. However, it is recommended to combine non-conventional energy sources to power desalination to overcome the energy shortages facing this country.
Keywords: Desalination plants; Reverse osmosis; Brackish water; Seawater; Jordan; REVERSE-OSMOSIS DESALINATION; BRACKISH-WATER; PERFORMANCE EVALUATION; ENERGY SYSTEM; PILOT-PLANT; WIND; PROJECT